Langerhans Cell Histiocytosis of the Cranial Base: Is Low-Dose Radiotherapy Effective? - Andreas Meyer; Michael Stark; Johann H. Karstens; Hans Christiansen; Frank Bruns (Case Reports in Oncological Medicine)
Introduction. Langerhans cell histiocytosis (LCH) is a rare disease of unknown etiology with different clinical features. A standardised treatment has not been established so far. Case Report. We report a case of a 28-year-old patient who initially presented with hypesthesia of the fifth cranial nerve and pain of the left ear. Diagnosis showed a tumour localised in the cranial base with a maximum diameter of 4.1 cm. The diagnosis of LCH was confirmed histologically by biopsy. Diagnostic workup verified the cranial lesion as the sole manifestation of LCH. A total dose of 9 Gy (single dose 1.8 Gy) was delivered. The symptoms dissolved completely within 6 months after radiation; repeated CT and MRI scans revealed a reduction in size of the lesion and a remineralisation of the bone. After a followup of 13 years the patient remains free of symptoms without relapse or any side effects from therapy. Discussion. Due to the indolent course of the disease with a high rate of spontaneous remissions the choice of treatment strongly depends on the individual clinical situation. In the presented case low-dose radiotherapy was sufficient to obtain long-term local control in a region with critical structures and tissues.